Using CFD to understand the effects of seam geometry on soccer ball aerodynamics - Fozzy Moritz, E.; Haake, S.; Barber, S.; Haake, S. J.; Carre, M. (The Engineering of Sport 6, Volume 2 Developments for Disciplines, 2006)
As the performance of athletes and their equipment is pushed to new limits, the importance of understanding the behaviour of sports balls is becoming increasingly apparent. Athletes and equipment manufacturers may try to maximise the distance travelled by a ball (e.g. golf, rugby) or unexpectedly swerve a ball to deceive the opposition (e.g. soccer, cricket, baseball). It is known that the surface geometry, spin and Reynolds number of a ball greatly affect its flight through the air, and this work focuses on understanding the effects of surface geometry. Computational Fluid Dynamics (CFD) has been used to help with the design and development of sports balls, firstly by understanding the details of the flow close to the surface, and secondly by attempting to characterise the surface geometry. CFD studies have been conducted on a smooth sphere and four different soccer balls, including a 1/3 scale model soccer ball and a real ball. The results have been compared to previous wind tunnel results of these balls, and the drag coefficients show consistent trends. It was found that the seam width and sharpness have a large effect on the ball`s aerodynamic behaviour. Various other balls have been scanned and will be modelled in the future. These results will be combined with trajectory methods in order to accurately simulate the flight of any given sports ball through the air, with any given input condition.